Pengaruh Akuntansi Forensik, Audit Investigatif, Independensi, dan Skeptisme Profesional Terhadap Pengungkapan Fraud (Studi Pada BPKP Perwakilan Jawa Tengah) - Wahyuadi Pamungkas; Jaeni (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2022)
This study aims to determine the effect of Forensic Accounting, Investigative Auditing, Independence, and Professional Skepticism on Fraud Disclosure at the Representative of the Financial and Development Supervisory Agency (BPKP) of Central Java Province. The data in this study used primary data in the form of a questionnaire distributed to the respondent unit at the State Audit and Development Agency (BPKP) of Central Java Province. The data analysis technique used is a quantitative method where the results are expressed in numbers. The data were processed using SPSS version 26 with the results obtained that Investigative Audit and Professional Skepticism affect the disclosure of fraud. Meanwhile, Forensic Accounting and Independence do not affect fraud disclosure.